التنمية المحلية في إطار التجارب الدولية والخبرات الميدانية - بيصار، عبدالمطلب Bisar, Abdulmuttaleb; شريط، حسين الأمين Sherit, Hussein Alamin (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2018)
The aim of this study is to try to highlight the reality of local development in Algeria, by addressing the basics related to local development, and then to the models and basics on local development, to present the reality of local development in the light of international experiences and field experiences. Local development is based on the principle of stimulating the efforts of individuals and citizens to identify the problems of their regions and find appropriate solutions to these problems under the support of the central bodies in order to achieve comprehensive national development. In addition, local development is one of the tools used in Achieve comprehensive national development. One of the most important recommendations of the study is the need to shed more light on the financing of local development and its role in improving the living standards of citizens at the local level through conducting further studies and field research.
تهدف هذه الدراسة إلى محاولة إبراز واقع التنمية المحلية في الجزائر، وهذا من خلال التطرق إلى الأساسيات المتعلقة بالتنمية المحلية، ثم إلى نماذج وأساسيات حول التنمية المحلية، ليتم عرض واقع التنمية المحلية في ظل التجارب الدولية والخبرات الميدانية، ومن أبرز ما توصلت إليه الدراسة هو أن التنمية المحلية تعتمد على مبدأ استثارة جهود الأفراد والمواطنين في الكشف عن المشاكل التي تعاني منها مناطقهم وإيجاد الحلول الملائمة لهذه المشاكل في ظل دعم الهيئات المركزية بغية تحقيق تنمية وطنية شاملة، بالإضافة إلى أن التنمية المحلية تعتبر أحد الأدوات المستعملة في تحقيق تنمية وطنية شاملة. ومن أهم ما جاءت به الدراسة من توصيات هو ضرورة تسليط الضوء أكثر على تمويل التنمية المحلية ودورها في تحسين الإطار المعيشي للمواطن على المستوى المحلي من خلال إجراء المزيد من الدراسات والبحوث الميدانية.
Keywords: التنمية -- التنمية المحلية -- التمويل المحلي -- استراتيجيات التنمية المحلية